2019
DOI: 10.1016/j.landurbplan.2019.103593
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of changes in human physiological indicators observed in soundscapes

Abstract: The objective of this study was to determine changes in physiological indicators with time in different soundscapes and their correlation with the results of subjective restorative evaluation. Physiological indicators including the heart rate (HR), amplitude of the R-wave (ΔR), heart rate variability (HRV), electroencephalography alpha reactivity (α-EEG), electroencephalography beta reactivity (β-EEG), eye blink frequency (BF), respiratory frequency (RF), respiratory depth (RD), skin conductance level (SCL), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 32 publications
(27 reference statements)
5
44
0
Order By: Relevance
“…For further verification, we performed a paired t-test on the results, as seen in Table 4. We use the p-value of 0.05 to distinguish the level of significance [27,31,34]. The results of the t-test showed that alarm sounds had a significant influence on the three physiological indicators SC, SCT and SCL (p < 0.05) of children, which was basically consistent with the results of studies on EDA indicators and risk perception in adults [27,37,44].…”
Section: The Significance Of the Influence Of Alarm Sound On Differensupporting
confidence: 78%
See 4 more Smart Citations
“…For further verification, we performed a paired t-test on the results, as seen in Table 4. We use the p-value of 0.05 to distinguish the level of significance [27,31,34]. The results of the t-test showed that alarm sounds had a significant influence on the three physiological indicators SC, SCT and SCL (p < 0.05) of children, which was basically consistent with the results of studies on EDA indicators and risk perception in adults [27,37,44].…”
Section: The Significance Of the Influence Of Alarm Sound On Differensupporting
confidence: 78%
“…Of the 42 subjects, one had to go to a Taekwondo class and failed to complete all the experiments due to time conflicts, so the data of a total of 41 subjects were collected. A database containing the final results was created using IBM SPSS 25.0 [27,31,50,51] to evaluate the effect of different types of alarm sounds on the risk perception of the children in the evacuation experiments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations